SAMPURAGA: PENCIPTAAN OPERA BATAK - Enrico Alamo (LPPMPP Institut Seni Indonesia Padangpanjang, 2014)
Opera Batak Sampuraga is a play that began from the experience of seeing the site Sampuraga Hot Spring, located in the area Sirambas Mandailing-Natal, and stories are told from mouth to mouth (oral literature). Then rearrangement is done regarding characterization and the occuring event by using some structures of Indonesian modern theater. As Batak Opera has some similarities with the structure of Indonesian modern theater, Opera Batak Sampuraga as an object of art creation, experiences a touch of creativity with the presence of various elements of art from other regions; one of them is gundala-gundala, a traditional theater of Karo region. Sampuraga play is a human obsession and ambition in reaching their goals, which requires sacrifice, although it eventually leads a curse. Opera This play is presented through a realism approach with representation style. The form of tragedy is chosen because of the incident happening to two human beings; mother and child. This creation is important because Opera Batak Sampuraga is similar to the pattern and characterization of plays in Indonesian modern theater.